Vestibular Findings in Military Band Musicians - Zeigelboim,Bianca Simone (2014)
Introduction Exposure to music is the subject of many studies because it is related to an individual's professional and social activities. Objectives Evaluate the vestibular behavior in military band musicians. Methods A retrospective cross-sectional study was performed. Nineteen musicians with ages ranging from 21 to 46 years were evaluated (average = 33.7 years and standard deviation = 7.2 years). They underwent anamnesis and vestibular and otolaryngologic evaluation through vectoelectronystagmography. Results The most evident otoneurologic symptoms in the anamnesis were tinnitus (84.2%), hearing difficulties (47.3%), dizziness (36.8%), headache (26.3%), intolerance to intense sounds (21.0%), and earache (15.7%). Seven musicians (37.0%) showed vestibular abnormality, which occurred in the caloric test. The abnormality was more prevalent in the peripheral vestibular system, and there was a predominance of irritative peripheral vestibular disorders. Conclusion The alteration in vestibular exam occurred in the caloric test (37.0%). There were changes in the prevalence of peripheral vestibular system with a predominance of irritative vestibular dysfunction. Dizziness was the most significant symptom for the vestibular test in correlation with neurotologic symptoms. The present study made it possible to verify the importance of the labyrinthine test, which demonstrates that this population should be better studied because the systematic exposure to high sound pressure levels may cause major vestibular alterations.